Investigations and enforcement - Johnstone, Peter; Jones, Richard (London : Butterworths, 2001)
Especially designed to emphasise the relevant provisions and implications of the rulebooks with regard to investigations and enforcement procedures, this new title forms part of Butterworths new series of guides to the FSA regime.Investigations and Enforcement will help you steer your way around the relevant provisions of the Financial Services and Markets Act 2000. It explains the FSA's stated policy and rules in related areas and addresses the practical issues that arise, and gives suggestions on how to deal with these issues.
Includes index.
oif 25/02/15
Loan
Keywords: Financial services industry; Financial institutions